Changing frames of obesity in the UK press 2008–2017. (November 2020) - Baker, Paul; Brookes, Gavin; Atanasova, Dimitrinka; Flint, Stuart W.
Abstract: Obesity is a persistently newsworthy topic for the UK press and in recent years levels of coverage have increased. In this study, we examine the ways in which obesity has been framed by the press over a ten-year period (2008–2017), focussing both on areas of stability and change. The analysis is based on a 36 million-word database of all UK newspaper articles mentioning the words 'obese' or 'obesity' published within this time frame and draws upon techniques from corpus linguistics – a collection of computational methods for examining recurrent linguistic patterns in large bodies of language data. Our analysis shows that, over time, obesity is represented increasingly as a biomedical problem that is both caused and should be prevented by individual action. Meanwhile, focus on wider environmental determinants of health, including the role of Government and the food industry, decreases over time. In the paper, we situate these trends within the wider context of UK society and argue that they both represent the increasing dominance of neoliberal models of health but also have the potential to contribute to weight stigma and the blaming of individuals. Accordingly, it is argued that the press should seek greater balance in its reporting of the potential causes of and solutions to obesity, as well as closer alignment with scientific evidence. By doing so, the press could begin to report on obesity in a way that raises useful public awareness around the topic and which challenges some of the stigma that currently attends to this social justice issue. Highlights: British newspapers doubled the amount of reporting on obesity between 2008 and 2017. These newspapers increasingly emphasise individual factors like biology and personal choice when writing about obesity. Emphasis on political and social factors has decreased in news reporting on obesity over time. The newspaper depictions run counter to the Government's Foresight Report in 2007. These depictions are likely to result in increased stigma and discrimination of people with obesity in the UK.